Pengaruh Sales Growth Dan Thin Capitalization Terhadap Tax Avoidance Dengan Kepemilikan Institusional Sebagai Variabel Moderasi - Anggraini, Muthia Suci; Indrayani, Lioni (CV. ITTC INDONESIA, 2025)
This research aims to examine the effect of sales growth and thin capitalization on tax avoidance with institutional ownership as a moderating variable. The population used in this study is all energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period, with a sample size of 70 data obtained using a purposive sampling method based on certain criteria in accordance with the research objectives. This research is a quantitative study using secondary data in the form of financial and annual reports of energy sector companies that can be obtained through the Indonesia Stock Exchange (IDX) website, namely www.idx.co.id or through other sources such as the official website of each company. The research instrument used is the documentation method, and the analysis was carried out using multiple linear regression and moderation regression analysis (MRA) to test the role of institutional ownership as a moderating variable with the help of Eviews 12 software. The results of the study based on the f test indicate that sales growth and thin capitalization have a simultaneous effect on tax avoidance. Partially (t test) shows the results that sales growth has an effect on tax avoidance, while thin capitalization has no effect on tax avoidance. Then, based on the results of the MRA test, it shows that institutional ownership is not able to moderate the influence of sales growth and thin capitalization on tax avoidance.